Kontruksi realitas terhadap kritik kebijakan Pembatasan Sosial Berskala Besar (PSBB) Di Indonesia - Pertiwi, Indriani Dian; Dewi, Nurul Aulia; Manoppo, Purnamasari (Ridwan Institute, 2021)
Mass media in the middle of the community in providing information is very good both important because people have fast, precise and accurate information. Online media is an option to be able to information because according to reason and the pen many where and whenever. This research is further to provide an overview of the criticisms that occur in the Central Government related to the handling of Large-Scale Social (PSBB). Online media such as Tempo.com and Kompas.com frame the news for the criticism that the Central Government with the PSBB stipulates and the validity period of the economic sector. The decision made by the Governor of DKI Jakarta Anies Baswedan as a measure of handling the Covid-19 virus was postponed by the Minister of Health Terawan and the final result on April 07, 2020. This study uses descriptive qualitative method with framing analysis model by Robert N. Entman. As a result of this study, both Tempo and Kompas's online news media criticized the site created by the Central Government. The tempo of the central government's policy is convoluted and very bureaucratic in psbb policy. Meanwhile, Kompas, framing the president of the MCC, Sohibul Iman the four of them in the absence of command from the leadership of the Republic of Indonesia which is handling Covid-19 became sluggish.